Proceedings of the 1st International Conference on Intellectuals' Global Responsibility (ICIGR 2017) 2018
DOI: 10.2991/icigr-17.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Digital Age Literacy in Elementary School

Abstract: Abstract-In the 21st century Literacy can no longer be defined only to read and to write. The impact of rapid development in the information, then the literacy interpreted in several points of view, ranging from basic literacy point of view, science literacy, economic literacy, technology literacy, visual literacy, information literacy, multicultural literacy, to the point of view of global awareness. This is called digital-age literacy or often called multiliteracies. The discussion of literacy widespread, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
3
Order By: Relevance
“…Changes in teaching styles also require applying technology in learning at all levels, including elementary school (Batty, Chelsea, 2020). In elementary school e-ISSN: 2656-6621 http://jurnal.uns.ac.id/Teknodika 94 TEKNODIKA students, literacy skills or digital age literacy is an ability that must be programmed, including basic literacy, scientific literacy, economic literacy, digital literacy, information literacy, multicultural literacy, and global awareness (Nuroh, Ermawati Z. Vevy Liansari, 2017). The application of the digital literacy curriculum in the education implementation at all education levels and types is as table 1: The article analysis revealed that in making digital literacy into the curriculum, it was done by incorporating digital literacy into all areas in the school or subject and making digital literacy, divided into two domains: media and technology, separate.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in teaching styles also require applying technology in learning at all levels, including elementary school (Batty, Chelsea, 2020). In elementary school e-ISSN: 2656-6621 http://jurnal.uns.ac.id/Teknodika 94 TEKNODIKA students, literacy skills or digital age literacy is an ability that must be programmed, including basic literacy, scientific literacy, economic literacy, digital literacy, information literacy, multicultural literacy, and global awareness (Nuroh, Ermawati Z. Vevy Liansari, 2017). The application of the digital literacy curriculum in the education implementation at all education levels and types is as table 1: The article analysis revealed that in making digital literacy into the curriculum, it was done by incorporating digital literacy into all areas in the school or subject and making digital literacy, divided into two domains: media and technology, separate.…”
Section: Resultsmentioning
confidence: 99%
“…Hal tersebut digunakan untuk menyediakan akomodasi dan modifikasi untuk kebutuhan pembelajaran yang beragam bagi peserta didik generasi Z. Literasi telah menjadi lebih dari sekedar kemampuan untuk membaca kata-kata tertulis dan definisinya terus berkembang dan bersifat paralel dengan perubahan dalam masyarakat, budaya, dan pendidikan (Iinuma, 2016;Tyner, 2009). Definisi telah mencakup deskripsi instruksi tradisional atau arahan dari keterampilan soal keaksaraan yang lebih dari standar minimum yang didefinisikan secara luas untuk pelajar abad ke-21 terutama generasi Z (Nuroh & Liansari, 2018;Tyner, 2009). Kemampuan literer atau keaksaraan terkait IPS tidak terbatas pada penguasaan kosakata, keterampilan perpustakaan dan referensi, strategi membaca, namun lebih pada siswa untuk menjadi pemikir mandiri dan pembelajar yang dapat mengingat dan menggunakan kembali apa yang telah mereka baca untuk mengumpulkan makna, berpikir kritis, dan memecahkan masalah adalah bagian dari literasi, yang tidak hanya melibatkan membaca, tetapi juga berbicara, mendengarkan, melihat, dan memahami semua bentuk materi yang terjadi dalam sosial masyarakat sekitar (Chapin, 2014;Kosnik et al, 2016;Tyner, 2009).…”
Section: Kajian Teoretisunclassified
“…Namun dalam konteks pendidikan IPS di SD, literasi mengalami perluasan makna di luar membaca dan menulis, terutama soal isu-isu dalam pembelajaran IPS. Pembelajaran IPS dalam gerakan literasi SD adalah keterampilan yang memungkinkan peserta didik membaca dunia tidak hanya melalui kata, kalimat, paragraf, atau wacana (Kosnik et al, 2016;Nuroh & Liansari, 2018). Literasi SD saat ini sudah memasuki arena literasi digital, dengan melibatkan penggunaan berbagai bentuk komunikasi yang memberikan kesempatan lebih jauh dan lebih besar untuk memajukan diri sendiri, lingkungan sekitar, dan masyarakat (Brugar & Roberts, 2018).…”
unclassified
See 1 more Smart Citation
“…Children are accustomed to using digital devices so that children get used to and have control over themselves [54], 5). Inserting digital literacy material in the curriculum as an early learning effort [7], through habituation activities [10]; and repetition [55] carried out by all stakeholders such as schools, teachers and parents [56]. So that the concept of digital literacy will grow and become a skill for elementary school students in Malang City.…”
Section: MXmentioning
confidence: 99%